Use of Rift Valley fever decision support tools led to improved interventions benefitting an estimated 3.1 million smallholders in Kenya - CGIAR Research Program on Agriculture for Nutrition and Health (2017)
ILRI developed and disseminated refined risk maps and a decision support framework for guiding decision-making processes in the prevention and control of Rift Valley fever (RVF). The Department of Veterinary Services in Kenya incorporated these tools into their national RVF contingency plan and also used them to implement risk-based RVF interventions. Improved control of RVF in animals would limit human infections and hence safeguard health and wellbeing of the local communities in 22 counties with high RVF risk in Kenya.